Peripheral fibroma/fibrous epulis with and without calcifications. a clinical evaluation of 204 cases in Singapore - Zain, R.B.; Fei, Y.J. (Edition Communication (N G -Com), 1990)
Peripheral fibroma/fibrous epulis accounts for the great majority of localised gingival swellings as was substantiated by various reports in the literature. A study was undertaken to investigate the clinical features of a series of 204 localised fibrous gingival swellings received by the Histopathology Laboratory, Department of Oral Surgery, National University of Singapore. The female patients were more affected than the male patients and the lesions occurred predominantly among the Chinese. The lesions were mainly pedunculated and most commonly occurred in anterior maxilla. The recurrence rate was about 10.3. In conclusion the results obtained in this study were overall in agreement with those of other authors.